Fuzzy algebraic hyperstructures : an introduction - Davvaz, Bijan; Cristea, Irina (Cham : Springer, 2015)
This book is intended as an introduction to fuzzy algebraic hyperstructures. As the first in its genre, it includes a number of topics, most of which reflect the authors' past research and thus provides a starting point for future research directions. The book is organized in five chapters. The first chapter introduces readers to the basic notions of algebraic structures and hyperstructures. The second covers fuzzy sets, fuzzy groups and fuzzy polygroups. The following two chapters are concerned with the theory of fuzzy Hv-structures: while the third chapter presents the concept of fuzzy Hv-subgroup of Hv-groups, the fourth covers the theory of fuzzy Hv-ideals of Hv-rings. The final chapter discusses several connections between hypergroups and fuzzy sets, and includes a study on the association between hypergroupoids and fuzzy sets endowed with two membership functions. In addition to providing a reference guide to researchers, the book is also intended as textbook for undergraduate and graduate students.
Fundamentals of algebraic (hyper)structures -- Fuzzy polygroups -- Fuzzy Hv-subgroups of Hv-groups -- Hv-rings (hyperrings) and Hv-ideals -- Connections between hypergroups and fuzzy sets.
Includes bibliographical references : pages [229]-238 and index.
Keywords: Fuzzy sets; Fuzzy mathematics